Right coronary artery deformation and injury following tricuspid valve surgery - Gerçek, Muhammed; Omran, Hazem; Friedrichs, Kai P.; Bleiziffer, Sabine; Gummert, Jan; Rudolph, Volker; Deutsch, Marcus A.; Rudolph, Tanja K. (Frontiers in Cardiovascular Medicine, 2022)
Background: Due to its close anatomical proximity to the annular plane of the tricuspid valve (TV), the right coronary artery (RCA) is at risk of injury and distortion during surgical and interventional repair. Recently, reversible, non-flow limiting, purse-string like deformations of the RCA following percutaneous TV annuloplasty have been described. In contrast, there are only anecdotal reports on RCA deformation following conventional TV surgery. Methods: A retrospective analysis of all patients undergoing TV surgery in our hospital between 2009 and 2019 was performed including all patients who received a post-operative coronary angiography (POCA). Angiographic footage was reviewed for RCA affections. Results: A total of 1383 patients underwent TV surgery (replacement and repair) for tricuspid regurgitation in our center. TV repair was performed in 1248 (90.2%) patients and 135 (9.8%) patients underwent isolated TV surgery. Sixty-five patients (4.7%) underwent POCA within 48 hours after surgery due to suspected myocardial ischemia, representing the final study population. Mean age was 70.3±11.3 years, 56.3% were female. Mean EuroSCORE II was 9.8±11.6%. Patients with the need for POCA due to suspected myocardial injury suffered from a higher mortality compared to event-free patients over the long-term follow up period (median 2.9years) regardless of the observed coronary status. RCA affections were observed in 24 (36.9%) patients. A new RCA deformation without flow-impairment or vascular damage was found in 16 (24.6%) of the cases and was managed conservatively. There was no significantly worse outcome observed as compared to patients without RCA affections. Six (9.2%) patients showed an RCA deformation accompanied by subtotal occlusion. A complete RCA-occlusion was observed in 2 (3.1%) patients. Revascularization by percutaneous coronary intervention could be successfully performed in these patients. RCA deformation occurred exclusively after TV repair while no cases were observed after TV replacement. Conclusion: RCA deformation without flow-limitation following surgical TV repair is a specific/typical phenomenon which might not impair patients’ outcome and could be managed conservatively in most of the cases. RCA injury indicating further interventional therapy is a rare complication of TV surgery. However, the need for immediate POCA in general appears to be associated with a worsened intermediate-term outcome.